Social Media Marketing Strategy on Tiktok Account @ngado.kado - Putri, Adin Kusno; Setyaningsih, Rila; Awola, Eunike Dina (PT FORMOSA CENDEKIA GLOBAL, 2025)
Research This aiming For know How social media marketing strategy on account tiktok @Ngado.kado. Study This use method descriptive qualitative with source of data obtained from results interviews , observations and documentation . Research This using the Social Media Marketing Theory put forward by Cris Heuer in the book Engage written by Brian Solis. Heuer stated that there are 4C elements in social media marketing, namely Context, Communications, Collaborations and Connections. The results of the study This state that give.a.gift has apply 4C elements in every activity marketing on account tiktok . First on the context element , ngado.kado do audience and trend analysis For determine use language, content message and creativity content. Second, in the communications element , ngado.kado apply communication with consumer through direct messages, comments and live streaming.